Sistemática de Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) - Nascimento, Jeane Marcelle Cavalcante do (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
The genus Simothraulopsis Demoulin belongs to the family Leptophlebiidae and only occurs in the Neotropical region. Currently it is represented by five species, but only three of these have the nymph described. In general, studies of the genus are spotty and provide little information on the biology of the different species and their distributions. In the present study we review current knowledge of Simothraulopsis and, based on specimens from different regions of Brazil, we add new taxonomic and biological information to this genus. A phylogenetic study was undertaken based on morphological data with the specific objective of evaluating the monophyly of Simothraulopsis and interespecific relationships within the genus. For this purpose, 46 characters related to external morphology of adults and nymphs were identified. The characters were evaluated by Fitch parsimony with equal weights and also successive weightings, and the resulting topologies were rooted a posteriori with an outgroup taxon. The analysis resulted in a single most-parsimonious tree and confirmed the monophyly of Simothraulopsis (supported by four synapomophies) and indicated the genus Homothraulus Demoulin, 1955 as the sister group. As a taxonomic result, four new species are described, increasing by 80% the number of representatives of the genus. Nymphs of Simothraulopsis diamantinensis Mariano, 2010 and Simothraulopsis janae Mariano, 2010 were described and the geographical distribution of the genus has been extended to several regions of Brazil. Previously, three of the five described species had only been recorded in their type localities. Detailed descriptions, including illustrations of structures not normally used in taxonomic studies on the family, diagnoses, biological comments and taxonomic keys for larvae and adults are integrated into the knowledge regarding the genus.
Keywords: Ephemeroptera Sistemática; Filogenia; Simothraulopsis